Implementasi Skema Junior Web Developer untuk Meningkatkan Kompetensi Siswa di SMK Negeri 1 Palangka Raya: Implementation of the Junior Web Developer Scheme to Improve Student's Competence at SMK Negeri 1 Palangka Raya - Herkules Herkules; Abdul Hadi; Christia Putra; Frengklin Matatula (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Based on the results of interviews conveyed by the Deputy Principal for the curriculum of the Palangka Raya State Vocational High School 1, he revealed that there was still a lack of interest in students to take part in national competency-based certification according to students' interests, even though the skill competency test was an assessment made to measure competency achievement according to Permendikbud No. 34 In 2018. This activity aims to introduce and prepare students to participate in the Junior Web Developer certification according to the Indonesian National Work Competency Standards in the form of hard and soft skills with lectures, practice, demonstrations, and problem-solving methods. The implementation of activities is carried out through three stages: the preparation stage, the activation process, and the evaluation. The activity starts with the pretest and ends with the post-test to determine the level of students' understanding. The assessment of activities based on the distribution of this activity questionnaire helped students improve their knowledge of web programming with the percentages of strongly agreeing 40.4%, agreeing 56.1%, and disagreeing 3.5%. While the evaluation results were based on comparing the pretest and post-test results, there was an increased understanding of the material presented in the first session. The percentage increase was 5%, the second session was 13%, the third session was 5%, and the fourth session was 11%. The post-test results showed 17 students who got passing grades in answering questions.